Antibiotic Resistance Pattern in First Year of Novel COVID-19 Era in a Metropolitan City in Bangladesh: A Retrospective Analysis - Arif, Mahmud Hassan; Tahreen, Taznuba; Ahmed, Rokshana; Ullah, Enshad Ekram; Sattar, Abdus (Journal of Chittagong Medical College Teachers' Association, 2023)
Background: Often bacterial infections cause illness and death all over the world. Selective pressure and increasing drug resistance are reportedly associated with the indiscriminate use of antibiotics to treat such illnesses. In this study our main goal is to evaluate the antibiotic resistance pattern in first year of novel COVID-19 era in a metropolitan city in Bangladesh. Materials and methods: This retrospective study was carried out at various pathology laboratories of Chattogram metropolitan city from March, 2020 to March, 2021. Total 5557 data were collected for this study. Results: During the study, Escherichia coli found to be most commonly isolated bacteria 32.8%. S. Typhi highly resistant to Azithromycin; 54%. Significantly high resistance rates observed of E. coli to azithromycin (68.5%). P. aeruginosa was highly resistant to Vancomycin (78%). Significantly high resistance rates of Klebsiella pneumoniae to Teicoplanin (75%). Staphylococcus was highly resistant to Vancomycin (78.1%). Enterococcus faecalis was highly resistant to Azithromycin (100%).Among the nine antibiotic ciprofloxacin created highest total resistance (31.86%). Conclusion: This study shows the main scenario of bacterial pathogens in different human specimen and their antibiotic resistance pattern during the COVID-19 epidemic. Gradual increase in number of E .coli and klebsiella organisms and their resistance to common antibiotics such as ampicillin, ciprofloxacin, cefuroxime were concerning issue in COVID-19 pandemic situation. JCMCTA 2023 ; 34 (1) : 41-46